HOW GOOGLE EARTH CALCULATES THE DISTANCE - Nur Islami (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2017)
Google Erath is a very useful application in the field of geology, geography and even in the field of social sciences. This article is an explanation on how Google Earth calculates the distance of a location to another location. When a position above the surface of Google Earth is determined, the latitude and longitude and altitude will be visible. To be able to calculate the distance of two locations requires the conversion of both locations for latitude, longitude and altitude into position x, y and z, where z coordinates is the average elevation measured from the sea surface. This conversion uses the basic science of spherical geometry and coordinate system. By using the manual calculation between the Rector building of Univeritas Riau in Pekanbaru to Monas in Jakarta, the distance of two locations is obtained of 954,239.5 m. The result of the conversion and distance calculation with this concept shows the value of almost equal to the distance measurements made by Google Erath which amounted to 953,065.1 m with the difference of around 0.123%. For the other 4 locations the percentage difference is almost equal to the average of 0.173%.